EFFECTS OF FIELD TRIP METHOD ON STUDENT’S ACADEMICACHIEVEMENT AND RETENTION IN BASIC SCIENCE AND TECHNOLOGY - Ekpo, Effiong Oji; Ehi, Ogar Margaret (IJRDO-Journal of Applied Science, 2022)
This study investigated the effects of field trip method on students’ achievement and retention in Basic Science and Technology among junior secondary school students in Yala, Cross River Nigeria. It also considered gender and cognitive ability levels of students as moderators. To achieve the objectives of this study three (3) research questions and three(3) null hypotheses were formulated to guide the study. A non-randomized pre-test post-test control group design was adopted for the study. The population size of the study was 3,546 while the sample size was 100 (52 males and 48 females), in two intact classes from two co-educational public secondary schools in Yala. The two classes were assigned to experimental and control groups respectively. Students in the experimental group were taught environmental hazards component using field trip method while the control group were taught using expository method. The instrument used for data collection was Basic Science and Technology Achievement Test (BSTAT) on environmental hazards. The instrument was validated and subjected to test-retest reliability. Its reliability co-efficient was 0.78, obtained using Pearson Product Moment Correlation (PPMC). The data obtained from the tests were analyzed using Analysis of Covariance (ANCOVA). All hypotheses were tested at 0.05 level of significance. The results showed that field trip had significant effect on students’ achievement. Also, students taught environmental hazards using field trip retained significantly higher than those taught with expository method. Gender had no significant effect on students’ achievement and retention in the concept of environmental hazards when taught using field trip method. There was significant effect of field trip method on students’ cognitive ability levels. Based on the findings, it was recommended among others that Basic Science and Technology teachers should use field trip method effectively in teaching environmental hazards component of Basic Science and Technology curriculum.